2014
DOI: 10.1186/bf03351732
|View full text |Cite
|
Sign up to set email alerts
|

Gravity inversion modeling across a 2-D dike-like structure—A Case Study

Abstract: Gravity investigations do have certain known limitations, the two most prominent perhaps being deep resolution and the non-uniqueness of the solution. We utilized the principle of the physical geometry a two-dimensional dike in the inversion process across tectonic line in the Chubu District, Honshu-in the Japan Alps. The location is probably where the Tsunan-Matsumoto tectonic line interacts with the Itoigawa-Shizuoka Tectonic Line (ISTL). Two-dimensional modeling results consistent with previous works on gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…By searching many papers related to our subject it can be found that their focus is on determining the parameters of dyke-like gravity sources (Bastani and Pedersen 2001;Abdelrahman and Essa 2007;Abdelrahman et al 2003, Asfahani andTlas 2007;Tlas and Asfahani 2011a, b;Cooper 2012Cooper , 2014Cooper , 2015 while it can be stated that dyke non-linear inverse modeling from gravity data less has been investigated. Ateya and Takemoto (2002) proposed a gravity inversion modeling across a 2-D dike-like structure. A fast simulated annealing global optimization technique has been proposed by Biswas (2016) to the interpretation of gravity and gravity anomaly over thin sheet-type structure.…”
Section: Introductionmentioning
confidence: 99%
“…By searching many papers related to our subject it can be found that their focus is on determining the parameters of dyke-like gravity sources (Bastani and Pedersen 2001;Abdelrahman and Essa 2007;Abdelrahman et al 2003, Asfahani andTlas 2007;Tlas and Asfahani 2011a, b;Cooper 2012Cooper , 2014Cooper , 2015 while it can be stated that dyke non-linear inverse modeling from gravity data less has been investigated. Ateya and Takemoto (2002) proposed a gravity inversion modeling across a 2-D dike-like structure. A fast simulated annealing global optimization technique has been proposed by Biswas (2016) to the interpretation of gravity and gravity anomaly over thin sheet-type structure.…”
Section: Introductionmentioning
confidence: 99%
“…Gravity method is a non-ruinous geophysical procedure that measures contrasts in the gravitational field of the earth at many various areas. It has much beneficial utilization in hydrocarbon exploration, mineral prospecting, archeological investigations, environmental applications and crustal imaging [1][2][3][4][5][6][7][8][9][10][11]. The main objective of the gravity interpretation is evaluating the model parameters (depth, amplitude coefficient, origin location, and shape parameter) of gravity oddities delivered by basic geometrical formed structures (spheres, cylinders).…”
Section: Introductionmentioning
confidence: 99%
“…Gravity and magnetic methods have many successful applications in mineral prospecting, environmental applications, and crustal imaging (e.g., Abdelrahman et al 1989;Ateya and Takemoto 2002;Batista-Rodríguez et al 2013;Beiki and Pedersen 2011;Fedi 2007;Hinze 1990;Hinze et al 2013;LaFehr and Nabighian 2012;Long and Kaufmann 2013;Mehanee 2014a;Nettleton 1976;Okubo et al 2013;Paoletti et al 2013;Pei et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques (e.g., Ateya and Takemoto 2002;Mushayandebvu et al 2001;Sazhina and Grushinsky 1971) are applied to obtain the characteristic inverse parameters of the underlying target.…”
Section: Introductionmentioning
confidence: 99%